2005
DOI: 10.1002/cne.20674
|View full text |Cite
|
Sign up to set email alerts
|

Effect of unilateral noise exposure on the tonotopic distribution of spontaneous activity in the cochlear nucleus and inferior colliculus in the cortically intact and decorticate rat

Abstract: Effects of unilateral noise exposure on spontaneous activity (SA) in the anteroventral and dorsal cochlear nuclei (AVCN and DCN) and the central nucleus of the inferior colliculus (ICc) were studied in cortically intact and decorticate rats. SA was measured 1 week following exposure using uptake of 14C-labeled 2-deoxyglucose (2DG) in quiet. Optical density (OD) measurements were obtained in low- and high-frequency (LF and HF) areas of each nucleus. We refer to the ipsilateral AVCN and DCN (side of the noise-ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 76 publications
3
26
0
Order By: Relevance
“…Salvi et al (1978) reported a decrease in spontaneous firing rates in VCN, but this study only measured activity a short time after a relatively mild sound exposure and measured mainly from low-frequency neurons (64% lower than 4 kHz). Imig and Durham (2005) reported alterations in the regional distribution of deoxyglucose uptake in cat VCN 1 week after unilateral noise exposure, but changes in absolute levels of uptake were not evident. Another indirect measure of neural activity, manganeseenhanced magnetic resonance imaging, was reported by Brozoski et al (2007), who showed increases in posteroventral cochlear nucleus in rats with behaviorally demonstrated tinnitus.…”
Section: Introductionmentioning
confidence: 90%
“…Salvi et al (1978) reported a decrease in spontaneous firing rates in VCN, but this study only measured activity a short time after a relatively mild sound exposure and measured mainly from low-frequency neurons (64% lower than 4 kHz). Imig and Durham (2005) reported alterations in the regional distribution of deoxyglucose uptake in cat VCN 1 week after unilateral noise exposure, but changes in absolute levels of uptake were not evident. Another indirect measure of neural activity, manganeseenhanced magnetic resonance imaging, was reported by Brozoski et al (2007), who showed increases in posteroventral cochlear nucleus in rats with behaviorally demonstrated tinnitus.…”
Section: Introductionmentioning
confidence: 90%
“…By contrast, autoradiographic imaging lacks physiological detail but can provide a more complete picture of activity levels in the major auditory nuclei. When this approach was used to measure the effects of unilateral sound exposure (Imig and Durham, 2005), the tonotopic distribution of 2-deoxyglucose (2DG) labeling was strongly correlated in the DCN, AVCN, and contralateral ICC. These results provide another source of support for the physiological links between midbrain activity and ascending inputs from the cochlear nucleus.…”
Section: Conditionmentioning
confidence: 99%
“…This condition of hyperactivity resembles activity that is elevated during sound stimulation and therefore seems a likely candidate for a tinnitus-producing signal. Sound-induced hyperactivity has now been observed in numerous other species including rats , chinchillas (Brozoski et al, 2002), guinea pigs (Imig and Durham, 2005) and mice (Kaltenbach et al, 2001). Hyperactivity has been induced in the DCN following prolonged exposure to both moderate and intense sounds, has been observed at both the single and multiunit levels Brozoski et al, 2002), and is not the result of increased activity in the auditory nerve (Zacharek et al, 2002;Liberman and Dodds, 1984).…”
Section: The Dcn and The Auditory Component Of Tinnitusmentioning
confidence: 99%